2009
DOI: 10.1007/s11748-008-0337-5
|View full text |Cite
|
Sign up to set email alerts
|

Role of salvage esophagectomy after definitive chemoradiotherapy

Abstract: Chemoradiotherapy has become a popular definitive therapy among many patients and oncologists for potentially resectable esophageal carcinoma. Although the complete response rates are high and short-term survival is favorable after chemoradiotherapy, persistent or recurrent locoregional disease is quite frequent. Salvage surgery is the sole curative intent treatment option for this course. As experience with definitive chemoradiotherapy grows, the number of salvage surgeries may increase. Selected articles abo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 42 publications
1
34
0
3
Order By: Relevance
“…The local recurrence rate at the first site was reported to be approximately 44-61% [1,2]. All patients with locoregional recurrence died within 1 year without treatment [3]. If recurrence occurs, the 5-year survival rate drops to 0-11% [4-6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The local recurrence rate at the first site was reported to be approximately 44-61% [1,2]. All patients with locoregional recurrence died within 1 year without treatment [3]. If recurrence occurs, the 5-year survival rate drops to 0-11% [4-6].…”
Section: Introductionmentioning
confidence: 99%
“…Long-term survival after salvage esophagectomy was related to resection without residual tumors (R0). The 5-year survival rate after salvage esophagectomy was reported to be up to 25-35% [3,7]. For unresectable or medically inoperable esophageal cancer, best supportive care is recommended (including external beam radiation therapy, intraluminal brachytherapy, chemotherapy, hyperthermia, laser, dilatation, endoscopic mucosal resection, and stent insertion) [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Although patients with EC receiving NCRTS had higher SRs compared with patients with non-NCRTS, some studies indicated that patients who underwent NCRT after esophagectomy were inclined to higher incidences of morbidity and mortality. [10114043] Furthermore, complications and toxicity of NCRTS effectuated a negative impact on higher postoperative mortality and morbidity. [1144] These findings were ascribed to the nature of the selected patients and sample size; hence, a contradictive opinion in other studies has presented no increase in the incidence of postoperative mortality and morbidity, compared with the non-NCRTS group.…”
Section: Discussionmentioning
confidence: 99%
“…For example, high-dose radiation therapy could substantially increase the risk of esophageal stricture and/or perforation, a potentially life-threatening complication. In contrast, some studies presented that some patients were cured with salvage esophagectomy after CCRT, and long-term survival was not worse than expected [18,19]. …”
Section: Discussionmentioning
confidence: 99%